PENGARUH WAKTU PENGANGKUTAN ADUKAN BETON KE TEMPAT PENGECORAN TERHADAP KEKUATAN TEKAN - Helwiyah Zain (Jurnal Teknik Sipil Unaya, 2015)
There is still a lot of casting concrete implementation which is mixing location was far with the casting location, because the situation in the field there are many obstacles to implement it.  As a result, from the mixing place to a casting place take a long time, so long as transportation there is a process of hydration in the concrete, which can cause a decrease in the quality of the concrete. To determine the decreasing of concrete quality, the research conducted is to determine the effect of time between when the mixing process of the concrete to casting process. This study used 48 specimens were divided into two groups, namely 24 specimens using the time difference without rotation and 24 pieces again with rotation. Each specimen using the same water cement ratio (fas), namely 0.45. Each group was subdivided in 6 variations in the time between mixing and casting namely :. 0 minutes, 12 minutes, 24 minutes, 36 minutes, 48 minutes and 60 minutes witch each variation using 4 specimens. The result of compressive strength each specimen group, for group I (without rotation) is 348 kg / cm2 for 0 minutes, 342 kg / cm2 for 12 minutes, 333 kg / cm2 for 24 minutes, 322 kg / cm2 for 36 minutes, 310 kg / cm2 for 48 minutes, and 294 kg / cm2 for 60 minutes. For group II (with rotation) is: 338 kg / cm2 for 0 minutes, 336 kg / cm2 for 12 minutes, 333 kg / cm2 for 24 minutes, 329 kg / cm2 for 36 minutes, 324 kg / cm2 for 48 minutes , and 318 kg / cm2 for 60 minutes. The results showed that, for the concrete without rotation: compressive strength at 60-minute time delay decreased by 15.52% of normal concrete (0 minute delay), and to the mixing concrete with rotation, compressive strength on delay of 60 minutes decreased by 5.92 % of normal concrete (0 minute delay). These results indicate that the delay time without rotation the greater the loss quality of concrete.